Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1186/s12967-017-1177-9
|View full text |Cite|
|
Sign up to set email alerts
|

Partnering with patients in translational oncology research: ethical approach

Abstract: BackgroundThe research program CARPEM (cancer research and personalized medicine) brings together the expertise of researchers and hospital-based oncologists to develop translational research in the context of personalized or “precision” medicine for cancer. There is recognition that patient involvement can help to take into account their needs and priorities in the development of this emerging practice but there is currently no consensus about how this can be achieved. In this study, we developed an empirical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…• Research process could expose patient partners to incidental findings on other patients' health [25,31].…”
Section: Research Step: Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…• Research process could expose patient partners to incidental findings on other patients' health [25,31].…”
Section: Research Step: Data Analysismentioning
confidence: 99%
“…Principles of research ethics are included in national and institutional guidelines and are implemented by institutional research ethics boards (REBs) and researchers. In our scoping review, we have identified only 5 issues (n = 5) associated with [25,30], or may expose patient partners to incidental findings about patient participants [25,31].…”
Section: Ethical Framework For Patient Partnership In Researchmentioning
confidence: 99%
“…Some have suggested the development of “translational ethics” that involves the patients as much as possible in the research and clinical processes. One successful study, CARPEM, formed a patient committee group tasked with designing a pamphlet explaining the informed consent process in a patient-friendly manner 170 . Others have suggested updating the “social contract” between clinicians, researchers, patients, and society as a whole 171 .…”
Section: Broader Consequences Of Ppmmentioning
confidence: 99%
“…The University of Coimbra brought experiences accumulated since its foundation in 1290, whereas the University of São Paulo was founded in 1935. The working group and others 5 , 6 reported a growing trend of academic partnerships between U.S., Canadian, and European health science institutions and AHCs from low- and middle-income countries. Research has been identified as one of the main reasons of this global movement and will gain increasing importance.…”
Section: The Importance Of An International Networkmentioning
confidence: 99%